The Role of Community Health Workers in Preventing Adolescent Repeat Pregnancies and Births - Maravilla, J.; Betts, K.; Abajobir, A.; Couto e Cruz, C.; Alati, Rosa (Elsevier, 2016)
© 2016 The Society for Adolescent Health and Medicine Intervention by community health workers (CHWs) is believed to prevent repeated childbearing among teenagers. This review investigated the effectiveness of CHWs in reducing repeated pregnancies and births among adolescents aged <20 years, 2 years after the delivery of their first child. Through electronic database and hand searching, experimental and/or observational studies were screened with their results undergoing systematic review and meta-analyses. Subgroup analyses were performed to further assess how study characteristics affected the pooled estimates and heterogeneity. A total of 11 eligible articles, from January 1980 to May 2015, were included. Seven studies evaluated repeated births and eight measured repeated pregnancies. Studies showed relevant disparities in terms of selected methodological aspects and program characteristics. Although most studies (n = 9) were either of “strong” or of “moderate” quality, only two of five finding a significant reduction exhibited a high level of quality as the other three failed to adjust results for confounders. Random effects modeling revealed an overall 30% decrease in repeated adolescent births (odds ratio =.70, confidence interval =.49–.99) among CHW-visited areas relative to nonvisited sites. On the other hand, no significant association was detected in terms of repeated pregnancies (odds ratio =.96, confidence interval =.70–1.28).